Evaluation of Newborn Care Corners in 24 by 7 PHCs of Bhavnagar District, Gujarat - Harsha M Solanki; Disha P Mehta; Manindra P Singh (Medsci Publications, 2019)
Background: As per Facility Based Newborn Care guidelines, Newborn Care Corner (NBCC) is mandatory at all delivery points which provide immediate care to newborns including initial care  to sick newborns. To provide quality newborn care there is need for evaluation of facility-based interventions. Methods: A cross-sectional study was conducted in all (eleven) 24X7 PHCs of Bhavnagar district during June 2014 - November 2014. Evaluation of NBCCs at PHCs was carried out using Dona- bedian Model having three parts. Input included facility level as- sessment, Process included quality care given to 33 newborns (ei- ther observing deliveries or interviewing mothers) and Output in- cluded mortality and morbidity data review. Results: All PHCs had NBCC however only 27.3% had beds for newborn care. FBNC services required at NBCC were available in all PHCs except referral facilities by own vehicle (available in 36.4% PHCs). Most of PHCs were having MBBS doctors (81.8%) while AYUSH MOs were found in 63.6% PHCs. Very few PHCs (27.3%) had staff nurse. Most of equipments required for newborn care were available and functional in majority PHCs except few monitoring and resuscitation equipments. All drugs, vaccines, lo- gistics were available at all PHCs. Delivery and newborn register were available and maintained at all PHCs. Only 45.5% PHCs were having death register. All newborns were given essential care services except eye care. Mortality record was nil and morbidity record included only Low birth weight. (Previous month data) Conclusion: Existing gaps in services, staffs, equipments, mainte- nance of registers and records should be looked for optimum func- tioning of NBCC.